Developmental competence of IVF and SCNT goat embryos is improved by inhibition of canonical WNT signaling - Marjan Sadeghi; Mohsen Rahimi Andani; Mehdi Hajian; Nafiseh Sanei; Reza Moradi-Hajidavaloo; Nasrin Mahvash; Farnoosh Jafarpour; Mohammad Hossein Nasr-Esfahani (PLoS ONE, 2023)
The specific role of the canonical WNT/β-catenin signaling pathway during the preimplantation development of goat remains unclear. Our objective was to investigate the expression of β-CATENIN, one of the critical components of Wnt signaling pathway, in IVF embryos and compare it with SCNT embryos in goat. In addition, we evaluated the consequence of inhibition of β-catenin using IWR1. Initially, we observed cytoplasmic expression of β-CATENIN in 2 and 8–16 cell stage embryos and membranous expression of β-CATENIN in compact morula and blastocyst stages. Furthermore, while we observed exclusively membranous localization of β-catenin in IVF blastocysts, we observed both membranous and cytoplasmic localization in SCNT blastocysts. We observed that Inhibition of WNT signaling by IWR1 during compact morula to blastocyst transition (from day 4 till day 7 of in vitro culture) increased blastocyst formation rate in both IVF and SCNT embryos. In conclusion, it seems that WNT signaling system has functional role in the preimplantation goat embryos, and inhibition of this pathway during the period of compact morula to blastocyst transition (D4-D7) can improve preimplantation embryonic development.